PENYULUHAN BATASAN-BATASAN PENGGUNAAN GADGET PADA TINGKAT SEKOLAH DASAR - Fahreza Sitompul, Ibnu Rasyid Munthe, Fitri Aini nasution, Yona Melia, Abdillah Menri Munthe (PT.JNDI, JURNAL BIMA, 2024)
Currently, the use of gadgets has involved almost all ages, even elementary school children are familiar with using gadgets to play games. The development of gadgets has had a big impact on society, where previously elementary school children played games using various conventional gaming equipment, now they can easily play various games via gadgets. Gadgets, as electronic devices with a small form factor, are designed to provide specific solutions by combining advanced technology, and have a number of functions that are very helpful in various human activities. One of the main functions of gadgets is as an entertainment tool, especially for children who often use gadgets to play games. However, excessive use of gadgets can lead to addiction in children, which can have a detrimental impact on their development. Therefore, it is important to limit the use of gadgets so that children do not become addicted to them. These restrictions need to be implemented through the synergy of various parties, including educational institutions, parents and teachers. Educational institutions have a key role in providing education about the limits of gadget use. The curriculum must include children's understanding of when they should not use gadgets, when they can use gadgets within certain time limits, and how parents can provide the necessary guidance. The role of parents and teachers is very important in monitoring and guiding children to avoid gadget addiction. Discussion between parents and children regarding the time to use gadgets, both for playing games and for online learning activities, is very necessary. Apart from that, knowledge about the limits of gadget use must continue to be campaigned by various parties so that people become more aware of the impacts and risks of excessive gadget use. It is hoped that through this campaign and outreach, there will be positive changes in attitudes and behavior in elementary school children, leading to more responsible use of gadgets and awareness of the positive impact on themselves and the surrounding environment.